Determination of Gaseous Sulphides in the Black Liquor Pyrolysis Gas - Xiao, Ling; Nong, Guangzai; Lu, Bingchen; Huang, Lijie; Li, Shiqiang; Wang, Shuangfei (Asian Journal of Chemistry, 2013)
Black liquor pyrolysis gas contains a little amount of gaseous sulphides, which need to be removed before combusting in the gas turbine in black liquor gasification combined cycle (BLGCC) or feeding into the reactor of synthesis dimethyl ether. The current investigation was carried out to find methods to determine gaseous sulphides in the black liquor pyrolysis gas. The pyrolysis gas was absorbed with benzene and then the absorption solution was analyzed by a gas chromatography and weighty. The analyzed results are: (1) the concentrations of CH3SH, CS2, CH3SCH3, CH3SSCH3, COS and H2S in the pyrolysis gas are 2.89, 3.88, 8.32, 2.01, 0.080 and 4.65 mg/L, respectively. (2) The masses of CH3SH, CS2, CH3SCH3, CH3SSCH3, COS and H2S in the gasification gas account for (Wt %) 0.168, 0.226, 0.439, 0.117, 0.0047 and 0.271 % of the black liquor, respectively.